DESKRIPSI KESULITAN MEMBACA PERMULAAN SISWA KELASI SEKOLAH DASAR NEGERI 35 PONTIANAK SELATAN - Dominika Farida; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to describe the initial reading ability of the first graders of State Elementary School 35 South Pontianak and to describe what are the factors that cause difficulty in reading the beginning of grade I students of State Elementary School 35 South Pontianak. Qualitative data were obtained from the results of the students' initial reading ability test and the results of interviews by researchers with the homeroom teacher. Research instruments in the form of interviews, observations and documentation. Based on the results of the study, from 32 students it can be concluded that students' difficulties from the overall content aspect in the initial reading test were from the percentage results there were 10 people or 0.32% for the very capable category, 11 people or 0.34% of the able category, 6 people or 0.18% for the moderately able category, and 5 people or 0.15% for the poor category. Factors that affect early reading ability are physical health factors, neurological factors, gender factors, intellectual factors, environmental factors such as social and economic factors for students' families, psychological factors including motivation and interest as well as psychological factors. It turns out that not all factors occur in the field, as for the factors that do not affect the reading ability of students at 35 South Pontianak Elementary School, namely the gender factor.Keywords: Beginning, Difficulty, Read